Harnessing the Potential of Synbiotic Therapy for Childhood Malnutrition: A Narrative Review of Onion Inulin Extracts and Probiotic-Rich Dadih - Refa Rahmaddiansyah; Wahida Rahmi; Dessy Arisanty; Rauza Sukma Rita; Sukarsi Rusti (Faculty of Medicine, Universitas Andalas, 2024)
Malnutrition and undernutrition in children are predominantly attributed to insufficient dietary intake and diseases, posing substantial risks without timely intervention. The emerging field of synbiotics, a symbiotic combination of probiotics and prebiotics, presents a promising avenue in nutritional therapy. It effectively modulates the composition and metabolic activities of the intestinal microbiota. This approach aligns seamlessly with the Sustainable Development Goals for 2030, offering a cost-effective strategy for both prophylaxis and immunomodulation. This study delves into a narrative literature review, examining the potential application of an extract derived from onion (Allium cepa Linn.) inulin, coupled with the beneficial attributes of the probiotic-rich traditional Sumatran dadih, as a supportive therapy. The emphasis lies in manipulating the intestinal microbiota and modulating the immune system, aiming to alleviate the severity of malnutrition-related complications in children. However, achieving optimal efficacy and safety with synbiotics necessitates further rigorous trials. These trials should specifically target refining dosage regimens and formulating compositions conducive to eliciting the desired, safe responses in clinical settings. In conclusion, the exploration of inulin sourced from onion extracts, integrated with supportive therapy focusing on gut microbiota manipulation and immune modulation alongside probiotic-rich dadih, shows immediate potential for practical application in addressing childhood malnutrition.